Bacillus Composted Paddy Husk as a Plant Nutrient Source to Promote Vegetative Growth and Nutrient Uptake in Maize: Bacillus composted paddy husk - CARLINA FREDDIE SIMOL; JOHN KEEN CHUBO; KHALID NAWI; IRA CARLBRENIE SIMOL (Borneo Journal of Resource Science and Technology, 2023)
Paddy husk (PH) is a waste generated from rice production that can be composted into organic fertiliser. Ligninolytic active Bacillus spp. from termite gut were added during the composting process to enhance the agronomic properties of compost produced from PH. This pot study was conducted using maize (Thai Super Sweet hybrid F1) as a test crop to determine the effects of using Bacillus composted PH in supplementing essential nutrients when used in tropical agricultural soil. A total of 144 planting pots, consisting of 12 treatments, were arranged in a Randomized Complete Block Design (RCBD) with three blocks, three replications and four sub-samples per replication. Maize growth namely plant height and leave number were recorded from 14 until 48 days after planting. Maize plants were harvested at 48 days after planting (tasseling stage) and total plant dry weights were recorded. Each plant part was ground and analysed for total N, P, K, Mg and Ca. Soil samples from the pots were sampled and analysed for TOC, pH, EC, total N, total P, available P, K, Mg and Ca. The results at 48 days after planting showed that Bacillus composted PH contributed to an increased by 24.29 to 31.67% in plant height, 53.84 to 61.61% in total plant dry weight and 9.09 to 16.67% in leaf number when compared to plants supplied with standard fertiliser. The use of Bacillus composted PH also improved soil pH, increased soil total N, total P, exchangeable K, Ca, and Mg. Maize treated with Bacillus composted PH showed higher nutrient uptake by 42.79 to 67.89% N, 30.05 to 56.25% P, 61.39 to 70.34% K, 47.39 to 69.94% Ca, and 76.62 to 83.74% Mg when compared to maize treated with standard fertiliser. This study suggests that Bacillus composted PH can promote vegetative growth in maize by acting as soil amendment and providing sufficient nutrients to the plant. Therefore, Bacillus composted PH has great potentials in promoting a more environmentally friendly and sustainable cropping practices which can benefit the environment and society.